The Agricultural Expansion in Conservation Areas: The Case of Gunung Halimun Salak National Park, West Java - Sardjo, Sulastri; Dharmawan, Arya Hadi; Darusman, Dudung; Wahyuni, Ekawati (Forestry Faculty, Universitas Hasanuddin, 2022)
The Indonesian government has expanded the Gunung Halimun Salak National Park (GHSNP) to reduce the impact of global climate change and conserve ecosystem biodiversity. This policy has been resisted by local communities who need access to GHNSP area to support their livelihoods. Qualitative and quantitative approaches have been applied in this study to explain the occurrence of agricultural expansion and its impact on the household economy in the GHSNP area. This study is supported by an analysis of secondary data regarding land cover changes in the GHSNP corridor area. This study found that farmers have been able to take reflexive and rational actions by utilizing power relations and social networks to regain their access in the GHSNP area. It was shown by the formation of concentrated agriculture expansion in areas that were previously stated as the forestry corporation concessions. Agricultural expansion has increased due to the economic needs of the resident, migration, and the resident's need for land. Massive agricultural expansion in the GHSNP corridor has changed land use and corridor landscapes and disrupted conservation goals. This study concludes that agricultural expansion occurred as a response of farmers to government decisions to expand the national park into areas the local communities considered part of their living space. The complexity of changes due to agricultural expansion in conservation areas challenges conservation experts and the forestry profession to develop adaptive management that is more sensitive to change and community needs.